Exploring the Impact of Sound Dampening Materials on Maritime Workers' Knowledge and Attitudes Towards Noise-Induced Hearing Loss: A Literature Review - Muhammad Zaidan Fadhlurrahman Rivlan; Yudhanto, Didit; Retno Setyowati, Ety; Herlina Sari, Nasmi (Journal of Fibers and Polymer Composites, 2024)
Effective mitigation strategies are necessary because high noise levels in maritime work situations frequently represent serious threats to hearing health. Acoustic panels and sound absorbers are examples of sound-dampening materials that are used to lower noise levels; nevertheless, it is unclear how these materials affect employees' awareness and attitudes. The purpose of this study is to investigate how the usage of sound-absorbing materials affects the attitudes and understanding of marine personnel about noise-induced hearing loss (NIHL). The study also covers ship personnel' attitudes toward NIHLs, their understanding of NIHLs, and their hazards. The strategies for increasing ship employees' understanding of and attitudes toward NIHL, the impact of sound-dampening materials on their knowledge and attitudes toward NIHL, and the effectiveness of NIHL awareness and training programs are also covered. While the majority of marine workers are knowledgeable that noise can lead to hearing loss, the review's findings show that their understanding of the causes and long-term consequences of NIHL is insufficient. Diverse perspectives exist regarding prevention, and several employees find it awkward to wear hearing protection. Sound-absorbing materials facilitate better communication and teamwork among employees, which can raise satisfaction at work and safety awareness while lessening the disruption caused by excessive noise. Moreover, employing hearing protection devices (HPPs) can raise staff members' awareness of NIHL and motivate them to utilize HPPs more proactively. These results provide recommendations for more potent preventive measures as well as significant insights into occupational safety and health regulations in the maritime sector.